1973
DOI: 10.1149/1.2403475
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Oxynitride Films from the NO-NH[sub 3]-SiH[sub 4] Reaction

Abstract: Silicon oxynitride films from the NO‐NH3‐SiH4 reaction in nitrogen at 850°C are clear, adherent, amorphous dielectrics whose composition may be varied over the entire range between SiO2 and Si3N4 by controlling the NH3/NO ratio employed. The refractive index is a convenient and accurate measure of the composition. Over much of the nitrogen‐rich range, the Si content is about 2% ower than stoichiometric, and the hypothesis is made that one nitrogen in three is bonded to only two other skeletal atoms ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 19 publications
(29 reference statements)
8
34
0
Order By: Relevance
“…If nitrogen existed as precipitated Si 3 N 4 the position of the Si-O-Si peak would not be expected to change. Rand and Roberts (1973) also observed a similar shift of the Si-O-Si stretching vibration to lower wavelengths in nitrided silicon thin films. XPS studies by Brow and Pantano also revealed that nitrogen is usually present in more than one form, and they proposed that non-bridging nitrogen ions may also be present, similar to the following:…”
Section: Nitrogen Coordination In Oxynitride Glass Structuressupporting
confidence: 59%
“…If nitrogen existed as precipitated Si 3 N 4 the position of the Si-O-Si peak would not be expected to change. Rand and Roberts (1973) also observed a similar shift of the Si-O-Si stretching vibration to lower wavelengths in nitrided silicon thin films. XPS studies by Brow and Pantano also revealed that nitrogen is usually present in more than one form, and they proposed that non-bridging nitrogen ions may also be present, similar to the following:…”
Section: Nitrogen Coordination In Oxynitride Glass Structuressupporting
confidence: 59%
“…Films obtained from low pressure chemical vapor deposition ͑LPCVD͒ have homogenous composition throughout the layer but the LPCVD process requires a high substrate temperature ͑800°C͒. 4,5 Microelectronic industries are actually looking for a lower temperature deposition process. The passivation must not modify the dopants profile and not induce new crystalline defects.…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of vibrations to wave numbers in several publications is summarized in Table 1 together with the references. Regardless of the interpretation of the structural background of the main IR absorption band of SiO X N Y films, many authors tried to find correlations between the peak position and the composition of the oxynitride films [10,14,23,[53][54][55], which by most authors is supposed to be rectilinear, between the peak position and the deposition parameters [27,56,57], or between the peak position and the physical properties [6,25,52,58,59]. In most publications, such a correlation is indicated, but not verified due to the low sample number or the lack in cross-checking.…”
Section: Infrared Spectrometrymentioning
confidence: 99%
“…With this background, NRA was the main tool used in this publication, because of the high sensitivity and selectivity that could be achieved by this method. The total amounts of 2 H (D), 14 N, 15 N, 16 O, and 18 O were determined using the cross-section "plateaus" of the following reactions: 2 H( 3 He,p) 4 15 N, were also mentioned. The total amount of 1 H was S. DREER AND P. WILHARTITZ detected by the resonance given above or by ERDA.…”
Section: Nuclear Reaction Analysismentioning
confidence: 99%